City planning and floods: The strategy of Montpellier. Issue 4 (19th June 2021) - Brun, Alexandre; Volle, Jean‐Paul
Abstract: Located between Marseille and Barcelona, Montpellier is one of the most attractive cities of the Mediterranean coast. It has more than 460, 000 inhabitants and grows by 7, 500 more inhabitants every year. This is largely due to its positive image and its freshly constructed neighbourhoods "Antigone" and "Port‐Marianne." From the late 1970s, the municipality's strategy was to organise the urban sprawl to the east and then towards the sea in the south of the city. The Lez, a small coastal river, well known for its spectacular flash floods, was the spine of this new urban growth. Internationally renowned architects and planners have been recruited to build these new "green" neighbourhoods (in French "éco‐quartiers") located on lands that used to be flooded regularly. This urban policy is largely due to the Montpellier's former mayor Georges Frêche and his deputy, the geographer Raymond Dugrand. The "urban planning" concept, or "urban design" projects, have largely been used by the local experts and officials to describe this development, but seem to be misused in this case. It has being mostly a political city‐project, still having the same objective as more than 30 years ago: to turn Montpellier towards the seaside. This paper will return to the strategy used at that time and, in retrospect, all the interrogations that have followed in terms of sustainable development and flood risk management. Abstract : Located between Marseille and Barcelona, Montpellier is one of the most attractive cities of the Mediterranean coast. From the late 1970s, the municipality's strategy was to organize the urban sprawl to the east and then towards the sea in the south of the city. The Lez, a small coastal river, well‐known for its spectacular flash floods, was the spine of this new urban growth. This paper will return on the strategy used at that time and, assess all the interrogations that have followed in terms of sustainable development and flood risk management.